The psychology of organizational change: new insights on the antecedents and consequences on the individual's responses to change - Oreg, Shaul; By, Rune Todnem; Michel, Alexandra (Cambridge University Press, 2023)
This volume brings together recent insights about the psychology of organizational change. The authors are leading scholars in the study of organizational change, taking on a micro-perspective for understanding the process through which responses to change emerge and impact work-related outcomes. Each chapter approaches the topic from a different perspective, highlighting a different aspect of the phenomenon. The book includes review chapters, chapters with new theoretical developments, and descriptions of empirical studies and their findings. It is intended for both academic and practitioners who wish to keep up to date about the mechanisms that explain how recipients of organizational change respond to and cope with change.
Title from publisher's bibliographic system (viewed on 29 Sep 2023)
Keywords: Aufsatzsammlung; Partizipation; Mitarbeiter; Organisationswandel